2015
DOI: 10.1161/jaha.115.002145
|View full text |Cite
|
Sign up to set email alerts
|

Post–Acute Care Data for Predicting Readmission After Ischemic Stroke: A Nationwide Cohort Analysis Using the Minimum Data Set

Abstract: BackgroundReducing hospital readmissions is a key component of reforms for stroke care. Current readmission prediction models lack accuracy and are limited by data being from only acute hospitalizations. We hypothesized that patient-level factors from a nationwide post–acute care database would improve prediction modeling.Methods and ResultsMedicare inpatient claims for the year 2008 that used International Classification of Diseases, Ninth Revision codes were used to identify ischemic stroke patients older th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 38 publications
7
35
2
4
Order By: Relevance
“…In contrast to our findings of higher rates of readmission and mortality among low‐volume centers, high‐volume teaching hospitals are more likely to incur Centers for Medicare and Medicaid Services reimbursement penalties for readmissions . Efforts to reliably identify patients with neurologic injuries at risk for readmission have proved challenging . Targeted multidisciplinary team‐based interventions to reduce preventable readmissions have proved beneficial for other conditions .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast to our findings of higher rates of readmission and mortality among low‐volume centers, high‐volume teaching hospitals are more likely to incur Centers for Medicare and Medicaid Services reimbursement penalties for readmissions . Efforts to reliably identify patients with neurologic injuries at risk for readmission have proved challenging . Targeted multidisciplinary team‐based interventions to reduce preventable readmissions have proved beneficial for other conditions .…”
Section: Discussioncontrasting
confidence: 82%
“…30 Efforts to reliably identify patients with neurologic injuries at risk for readmission have proved challenging. 31 Targeted multidisciplinary team-based interventions to reduce preventable readmissions have proved beneficial for other conditions. 32 Potentially important determinants for preventing readmission found in larger, highvolume hospitals include dedicated neurointensive care units, neuroscience-specialized nursing care, social work, case management, and rehabilitation services that may be important determinants of readmission for aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…7-11 In some of the stroke-specific studies, ethnic minorities have also been shown to have higher rates of 30-day readmission after stroke compared to non-Hispanic whites. 12, 13 However, the reported impact of ethnicity on 30-day readmission after stroke has been inconsistent 14 and remains unclear. Furthermore, there is paucity of data on stroke readmissions that have disaggregated Pacific Islanders from Asian Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke was recently added to the list of conditions in which 30dRAs are penalized by the ACA, which prompted numerous studies that analyzed readmission rates for various cerebrovascular insults [1,2,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Despite recent efforts, there remains limited knowledge regarding annual trends and risk factors for 30dRA among patients with spontaneous intracerebral hemorrhage (sICH).…”
Section: Introductionmentioning
confidence: 99%